Upaya Meningkatkan Hasil Belajar IPS Materi Konflik Dan Integrasi Dalam Kehidupan Sosial Melalui Model Pembelajaran Kooperatif Tipe STAD (Student Teams Achievment Division) Pada Siswa Kelas 8 C SMPN 13 Magelang Tahun 2022/2023 - Lestari, Yuni (Faculty Of Education, 2024)
Reality shows that social studies learning outcomes on Strengthening the Maritime Economy and This research aims to: (1) Describe the process of implementing the STAD (Student Teams Achievement Division) Cooperative learning model in improving social studies learning outcomes on Conflict and Integration in Social Life for Class 8C students at SMPN 13 Magelang. This research is Classroom Action Research which consists of 2 cycles, each cycle consisting of 3 stages, namely: Planning, Action and Observation, and Reflection. The research subjects were 35 students at SMP Negeri 13 Magelang. Data collection in this research used observation sheets and student assessment sheets. The data analysis techniques used are qualitative descriptive and quantitative descriptive. Based on the results of research and discussion, it was obtained that social studies learning data on Conflict and Integration in Social Life for class 8C students at SMPN 13 Magelang after implementing learning using the STAD (Student Team Achievement Division) Cooperative Learning model in cycle I was 77.12 on average after carried out in cycle II, the average was 81.37. These results show that the STAD (Student Teams Achievement Division) Cooperative learning model can IPS studies learning outcomes for class students at SMP Negeri 13 Magelang